Zebrafish Model as a Screen to Prevent Cyst Inflation in Autosomal Dominant Polycystic Kidney Disease - Oliveira, I (2021)
In autosomal dominant polycystic kidney disease (ADPKD), kidney cyst growth requires the recruitment of CFTR (cystic fibrosis transmembrane conductance regulator), the chloride channel that is defective in cystic fibrosis. We have been studying cyst inflation using the zebrafish Kupffer's vesicle (KV) as model system because we previously demonstrated that knocking down polycystin 2 (PC2) induced a CFTR-mediated enlargement of the organ. We have now quantified the PC2 knockdown by showing that it causes a 73% reduction in the number of KV cilia expressing PC2. According to the literature, this is an essential event in kidney cystogenesis in ADPKD mice. Additionally, we demonstrated that the PC2 knockdown leads to a significant accumulation of CFTR-GFP at the apical region of the KV cells. Furthermore, we determined that KV enlargement is rescued by the injection of Xenopus pkd2 mRNA and by 100 µM tolvaptan treatment, the unique and approved pharmacologic approach for ADPKD management. We expected vasopressin V2 receptor antagonist to lower the cAMP levels of KV-lining cells and, thus, to inactivate CFTR. These findings further support the use of the KV as an in vivo model for screening compounds that may prevent cyst enlargement in this ciliopathy, through CFTR inhibition.